Evaluation of Implementation of the Kentucky Court Rules of Procedure and Practice: An Approach to Assessing the Impact of Court Reform Efforts. (September 2015) - Boes, Corey; Collins‐Camargo, Crystal; Thomas, Tammi Alvey
Abstract: This article describes a Supreme Court of Kentucky court improvement initiative designed to promote uniformity and improved court practice with an ultimate goal of the improvement of outcomes for children and families through implementation of Family Court Rules of Procedure and Practice. Twelve jurisdictions were purposely selected to exhibit a range of family and non‐family court jurisdictions, rural and middle‐sized locations. This article focuses on the results of court case file review related to indicators of due process and timeliness. Implications for court evaluation and reform activities are discussed.